Fraxinellone Has Anticancer Activity by Inducing Osteosarcoma Cell Apoptosis via Promoting Excessive Autophagy Flux - He, Bin; Zhang, Wenkan; He, Jiaming (Frontiers in Pharmacology, 2021)
Osteosarcoma is a malignant bone tumor that is easy to metastasize in the early stage and has a very poor prognosis. Fraxinellone (FRA) is one of the main components isolated from the D. dasycarpus plant. Its anti-inflammatory and neuroprotective effects have been confirmed, but the research on the anti-cancer effect of FRA and its potential mechanism is relatively scarce. In this study, we found that FRA inhibited the proliferation and migration of osteosarcoma cells HOS and MG63 in a dose-dependent manner. Immunofluorescence, fluorescence staining and western blotting analysis showed that FRA could simultaneously induce osteosarcoma cell apoptosis and increase autophagy flux. Subsequent turnaround experiments suggested that the pro-apoptotic effect of FRA was achieved through excessive autophagy flux. The results of the xenograft orthotopic model further supported the anti-cancer effects of FRA, indicating that FRA treatment inhibited the growth of osteosarcoma, and the pro-apoptotic and autophagy effects of FRA were also proved in vivo. These studies provide new ideas for the future treatment of osteosarcoma and offer theoretical support for the anti-cancer mechanism of FRA.